HUBUNGAN CANVA DENGAN LITERASI DIGITAL MAHASISWA PGSD DI ERA ARTIFICIAL INTELLIGENCE (AI) - Fina Violina Herman; Laras Ramadhani; Jesi Alexander Alim; Mitha Dwi Anggriani (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the relationship between the use of Canva, an online graphic design application, and the digital literacy of Primary School Teacher Education (PGSD) students in the era of Artificial Intelligence (AI). The research employed a quantitative correlational approach using a Likert-scale questionnaire, with data analyzed through validity and reliability tests, product moment correlation, Spearman Rank correlation, and simple regression analysis. The results indicate that the level of Canva usage is categorized as high (95%), as well as students’ digital literacy (90%). The Spearman Rank correlation test yielded rs = 0.407, indicating a positive and moderate correlation between Canva usage and digital literacy. Furthermore, the coefficient of determination (R²) of 0.232 shows that Canva contributes 23.2% to digital literacy, while the remaining 76.8% is influenced by other factors beyond this study. These findings highlight that Canva is not only a design tool but also an effective digital learning medium to enhance students’ digital literacy. Therefore, Canva plays a crucial role in fostering students’ critical thinking, creativity, and collaboration skills, while also preparing them to face AI-based learning challenges.